Transitional Justice and Education Engaging Young People in Peacebuilding and Reconciliation - Ramirez-Barat, Clara; Schulze, Martina (2018)
This volume addresses the role and importance of education for processes of transitional justice. In the aftermath of conflict and mass violence, education has been one of the tools with which societies have sought to achieve positive transformation. While education has the potential to trigger, maintain, and exacerbate conflict, it has also been designed to promote a deeper, more nuanced understanding of the past and to advance reconciliation, peacebuilding, and prevention. The original contributions in the book reflect on lessons learned from education policies of the past in post-conflict societies and seek innovative, sustainable, and context-sensitive grassroots approaches, designed to advocate critical thinking, values of inclusion and tolerance, and ultimately a culture of peace.